Tissue Culture Strategies In Sugarcane (Saccharum Officinarum L.) - SWAPANIL YADAV,; AQUIL AHMAD,; JYOTI RASTOGI,; MADAN LAL, (International Journal of Pharma and Bio Sciences, 2012)
Sugarcane (Saccharum officinarum L.) has wide range of economic importance due to its major and by-products. Seed multiplication of newly released varieties of sugarcane is one of the major constraints. Once a desired clone is identified, it usually takes 6-7 years to produce sufficient quality of improved seed material. This long duration causes a major bottleneck in breeding programmes. For this reason, micropropagation offers a practical and fast method for mass propagation of clonal material. Limitations and time consuming conventional methods promoted the need of plant tissue culture and genetic engineering in sugarcane molecular breeding programmes. Plant tissue culture techniques have become a powerful tool for studying and solving basic and applied problems in plant biotechnology. Sugarcane is a suitable candidate for plant biotechnology and genetic engineering tool due to its complex genomic structure, poly-auenploidy, rare flowering, and poor fertility. Successful protocols for shoot tip culture, callus culture, embryo culture, virus free plant production, somatic embryogenesis and genetic transformation have been already established. Thus following technique can be used to enhance mass production of sugarcane crop economically with the present trend of demand of sugarcane in the region.